Réponses

2013-12-11T16:12:38+01:00
Bonjour,

Ces exercices sont des applications de la formule : (a + b)(a - b) = a² - b².

A = (x - 2)(x + 2)
   = x² - 2²
   = x² - 4.

B = (5 - y)(5 + y) 
   = 5² - y²
   = 25 - y²

C = (3x + 5)(3x - 5)
   = (3x)² - 5²
   = 9x² - 25

D = (10 - 7z)(10 + 7z)
   = 10² - (7z)²
   = 100 - 49z²

E = (5 + 4g)(5 - 4g)
   = 5² - (4g)²
   = 25 - 16g²

F = (2,1x - 3)(2,1x + 3)
   = (2,1)² - 3²
   = 4,41x² - 9

G = (2i + 6,1)(2i - 6,1)
   = (2i)² - 6,1²
   = 4i² - 37,21

H = (3,2j + 4)(4 - 3,2j)
   = (4 + 3,2j)(4 - 3,2j)
   = 4² - (3,2j)²
   = 16 - 10,24j²